Design and human–machine compatibility analysis of Co-Exos II for upper-limb rehabilitation. Issue 4 (2nd September 2019) - Zhang, Leiyu; Li, Jianfeng; Ji, Shuting; Su, Peng; Tao, Chunjing; Ji, Run
Abstract : Purpose: Upper-limb joint kinematics are highly complex and the kinematics of rehabilitation exoskeletons fail to reproduce them, resulting in hyperstaticity and human–machine incompatibility. The purpose of this paper is to design and develop a compatible exoskeleton robot (Co-Exos II) to address these problems. Design/methodology/approach: The configuration synthesis of Co-Exos II is completed using advanced mechanism theory. A compatible configuration is selected and four passive joints are introduced into the connecting interfaces based on optimal configuration principles. A Co-Exos II prototype with nine degrees of freedom (DOFs) is developed and still owns a compact structure and volume. A new approach is presented to compensate the vertical glenohumeral (GH) movements. Co-Exos II and the upper arm are simplified as a guide-bar mechanism at the elevating plane. The theoretical displacements of passive joints are calculated by the kinematic model of the shoulder loop. The compatible experiments are completed to measure the kinematics of passive joints. Findings: The compatible configuration of the passive joints can effectively reduce the gravity influences of the exoskeleton device and the upper extremities. The passive joints exhibit excellent compensation effect for the GH joint movements by comparing the theoretical and measured results. Passive joints can compensate for most GH movements, especially vertical movements. Originality/value: Co-Exos II possesses good human–machine compatibility and wearable comfort for the affected upper limbs. The proposed compensation method is convenient to therapists and stroke patients during the rehabilitation trainings.